An Interesting Case Of Concomitant Tuberculosis and Adenocarcinoma Colon - Monteiro, Rashmi; Agrawal, Preeti; Sujanani, Shashi; Vyas, K C (Annals of Pathology and Laboratory Medicine, 2020)
Abdominal tuberculosis and colon carcinomas are commonly seen in patients worldwide. However co-existing gastrointestinal tuberculosis and adenocarcinoma in the same site is unusual and is a rare entity. We here in report an interesting case of tuberculosis and adenocarcinoma occurring concomitantly in the colon, along with metastasis and caseating tuberculosis in mesenteric lymph nodes in a 73-years-old female presenting with pain in abdomen, vomiting and nausea.